The Effect of Papaya Seed Ethanol Extract in Vivo on The Number of Osteoblasts Cells of Periodontitis-Induced Rats - Ratih Pusporini; Ahmad Basori; Agung Krismariono (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
The papaya seed ethanol extract is rich in antioxidant ingredients, such as flavonoids and phenolic acids. One of the main factors causing chronic inflammatory in periodontitis is oxidative stress. Administration of papaya seed extract is assumed to increase the number of rat osteoblast cells induced periodontitis. This research was conducted to analyze the effect of papaya seed extract on osteoblasts cells of rat induced periodontitis. This research represented an experimental laboratory-based investigation involving 35 rats of the Rattus norvegicus strain divided into 5 treatment groups (K, P1, P2, P3, P4). Control group (K) was not induced by periodontitis and was not given an extract, while group P induced periodontitis using LPS Phorphyromonas gingivalis (P.gingivalis) for 7 days and continued wire mesh installation around the mandibular incisors in the form of number “8” for 7 days. P1 group was given feed only without extract, while the rest were given extract of 200 mg/kgBB, 300mg/kgBB, and 400mg/kgBB. The data obtained were analyzed with a one-way ANOVA test. The results showed that the average number of osteoblasts varied significantly between the groups. There was an increase in the average number of osteoblast cells in rat induced periodontitis after given papaya seed extract.